2005
DOI: 10.4049/jimmunol.175.3.1795
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Uterine Epithelial Cells Preferentially Present Antigen at the Basolateral Surface: Role of Stromal Cells in Regulating Class II-Mediated Epithelial Cell Antigen Presentation

Abstract: To study Ag presentation in the female reproductive tract, DO11.10 TCR transgenic mice specific for the class II MHC-restricted OVA323–339 peptide and nontransgenic BALB/c mice were used. We report here that freshly isolated uterine epithelial cells, uterine stromal, and vaginal APCs present OVA and OVA323–339peptide to naive- and memory T cells, which is reduced when cells are incubated with Abs to CD80 and 86. To determine whether polarized primary epithelial cells present Ags, uterine epithelial cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 59 publications
0
30
1
Order By: Relevance
“…It has been suggested that there is a site-specific mucosal immune system in the female upper genital tract that differs from that described in the gastrointestinal and respiratory tracts [185,186]. Furthermore, the immune system in the upper genital tract differs from that of the lower genital tract [14,[180][181][182][183][184][185][186]. The putative immune system in the upper genital tract appears to contribute to the maintenance of an aseptic milieu; that is, this immune system inhibits the growth of microorganisms that sporadically colonize this region [181,183].…”
Section: Immune System Modulationmentioning
confidence: 91%
See 3 more Smart Citations
“…It has been suggested that there is a site-specific mucosal immune system in the female upper genital tract that differs from that described in the gastrointestinal and respiratory tracts [185,186]. Furthermore, the immune system in the upper genital tract differs from that of the lower genital tract [14,[180][181][182][183][184][185][186]. The putative immune system in the upper genital tract appears to contribute to the maintenance of an aseptic milieu; that is, this immune system inhibits the growth of microorganisms that sporadically colonize this region [181,183].…”
Section: Immune System Modulationmentioning
confidence: 91%
“…The sequelae of such inflammation in the upper genital tract would be highly detrimental to the defense and reproductive functions of the mucosal surface [184]. If the protection afforded by the epithelial barrier is compromised, however, pathogens encounter a second layer of innate defense consisting of specialized immune cells and their products [180,181]. These cells, which include macrophages, dendritic cells, neutrophils, and natural killer cells, are dispersed throughout the female genital tract, surveying that environment [181].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…responses in the FRT are suppressed by a mechanism possibly acting through an APC, and this effect can be reproduced by estradiol treatment of ovariectomized (OVX) mice (32)(33)(34)(35). Intravaginal (IVAG) immunization during estrus (but not diestrus) also reduced subsequent delayed-type hypersensitivity responses (36).…”
Section: Seavey and T R Mosmann Unpublished Observations) Finallymentioning
confidence: 99%